An investigation of fundamental flow structures in ground effect with application to the development of brownout conditions in hover - Bourne, K.; Reddy, K.R.; Kumar, C.; Ooi, A. (My University, 2014)
The flow structures underlying the formation of toroid-like dust clouds during brownout are not well understood. This study sought to confirm the presence of persistent structures, referred to here as global recirculation, which would correlate with anecdotal evidence indicating such structures were stable rather than transient. Both stereo and planar Particle Image Velocimetry (PIV) was used to assess the flow beneath a sub-scale rotor model operating in ground effect. Results showed that a global recirculation flow structure could be generated at 200 and 300 RPM, and although persistent, there was evidence of the structure meandering over time.